Pendampingan Masyarakat untuk Ketahanan Pangan Berbasis Peternakan di Wilayah Penyangga Ibukota Negara Penajam Paser Utara, Kalimantan Timur: Community Assistance for Livestock-Based Food Security in the Capital City Support Area Penajam Paser Utara, East Kalimantan - Rudy Agung Nugroho; Retno Aryani; Julinda Romauli Manullang; Muhammad Fauzi Arif; Rudianto Rudianto; Suhardi Suhardi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The development of the Nusantara Capital City (IKN) in East Kalimantan has led to rapid urbanization and agricultural land conversion in buffer zones such as Penajam Paser Utara (PPU), thereby impacting local food security. This community service program, supported by the INUCOST project, aims to increase the knowledge of livestock farmers, farmers, and stakeholders in sustainable livestock-based food security. The activity was held on November 27, 2025, at the Petung Agricultural Extension Center Building, PPU, using participatory methods, including preparation (surveys and coordination) and implementation (presentations by speakers such as Prof. Rudy Agung Nugroho, Ph.D., Ir.). Andi Trasodiharto, M.Si., drh. Didik, and Ir. Julinda Manulang, MP; interactive discussions; field visits to Sutiman Farm for observations of sheep farming and goat milk production, as well as pre-post test evaluations and Likert questionnaires for around 50 participants from livestock, farming, and government agencies. The results showed an increase in understanding from 86.97 to 98.62 (13.39%) in 33 respondents, with the majority of questionnaire responses ranging from “good” to “very good” (55-82%). The discussion indicates moderate effectiveness due to a high initial knowledge base, but it is lower than that of similar community service programs (e.g., 42.83-55%). The community service program activities carried out strengthen local capacity, diversify animal protein (such as goat milk), and coordinate stakeholders. The benefits of these activities include strengthening regional food security and economic stability in the IKN buffer zone.